Exploring Past Images in a Digital Age Reinventing the Archive - Erdoğan, Nezih; Kayaalp, Ebru (Framing Film, 2023)
Film archives are fast spreading around the world, and with them issues surrounding archival digitisation, artistic appropriation, and academic reinterpretation of film material that demand scholarly attention. Exploring Past Images in a Digital Age: Reinventing the Archive aims to fill this demand with a thought-provoking collection of original articles contributed by renowned scholars, archivists, and artists. It urges the reader to "forget" standard ways of thinking about film archives and come to grips with the challenges of analysing and recontextualising an area in transit from the analogue to the digital. The book not only throws light on unexplored issues related to film archives but also introduces unconventional approaches and alternative sources for scholarly research and a vast range of artistic possibilities.